Culture's influence on consumers: exploratory behavior and risk taking - Soares, Ana Maria (2003)
This theoretical paper addresses the influence of culture on risk taking and exploratory behavior. The cultural dimensions of long-term orientation, power distance, uncertainty avoidance, collectivism, and masculinity (Hofstede, 1984, 2001) are hypothesized to influence risk-taking behavior in general, and, through it, exploratory consumption behavior, risk taking, and risk attitudes and perception towards specific products. We also propose an empirical study to test the emergent model.